Система збору даних про стан транспортних засобів - Мошкін, Д. С. (ХНУРЕ, 2024)
The report examines in detail the importance of the use of video recorders in cars and analyzes the possibility of creating a recorder that would be more functionally infected than those available. The author discusses the need to include additional vehicle information, such as speed, position, and turn indica tors, and points out the potential benefits of this improvement. The report also analyzes the possibility of reading data from the car's CAN bus and the variety of data exchange protocols that can be used for this. Finally, the author considers the principle of operation of differential signals on the CAN line and emphasizes their high reliability and stability.
Keywords: система збору даних; стан транспортних засобів